2013
DOI: 10.2478/s11756-013-0188-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable transformation and actin visualization in callus cultures of dodder (Cuscuta europaea)

Abstract: Agrobacterium tumefaciens-mediated transformation of callus culture, combined with a visual selection of GFPtagged fimbrin actin binding domain (FABD2) expression is described for parasitic species (Cuscuta europaea). The conditions for callus induction from 1 cm-long explants from the basal part of 7-day-old dodder seedlings were defined. We obtained light-green calli, which were transformed with A. tumefaciens bacterial strain GV3101 carrying plasmid pCB302 (35S::ABD2:gfp) with neomycin phosphotransferase (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…The main bottleneck is the lack of an efficient and reproducible protocol with which transgene expression or even genetic manipulations can be performed. Previous attempts to transform Cuscuta have shown that A. tumefaciens is able to transform callus cells (Borsics et al, 2002; Svubova and Blehova, 2013). However, in our hands these transformation events were very scarce, explaining maybe why this approach has not yielded greater success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main bottleneck is the lack of an efficient and reproducible protocol with which transgene expression or even genetic manipulations can be performed. Previous attempts to transform Cuscuta have shown that A. tumefaciens is able to transform callus cells (Borsics et al, 2002; Svubova and Blehova, 2013). However, in our hands these transformation events were very scarce, explaining maybe why this approach has not yielded greater success.…”
Section: Discussionmentioning
confidence: 99%
“…These are low transformation efficiencies on one hand and recalcitrance of callus propagation and shoot regeneration in vitro on the other hand. Few approaches to transform C. trifolii (Borsics et al, 2002) and C. europaea (Svubova and Blehova, 2013) have been reported. Explants from seedlings were transformed using Agrobacterium tumefaciens , and expression of the transgenes was demonstrated in the calli.…”
Section: Introductionmentioning
confidence: 99%
“…The main bottleneck is the lack of an efficient and reproducible protocol with which targeted genetic manipulations can be performed. Previous attempts to transform Cuscuta have shown that A. tumefaciens is able to transform callus cells (Borsics et al, 2002; Svubova and Blehova, 2013). However, in our hands these transformation events were very scarce, explaining maybe why this approach has not yielded greater success.…”
Section: Discussionmentioning
confidence: 99%
“…However, two significant bottlenecks to perform targeted genome manipulations remain in the form of low transformation efficiency and poor regeneration rates of Cuscuta tissues in vitro . Some few approaches to transform C. trifolii (Borsics et al, 2002) and C. europaea (Svubova and Blehova, 2013) have been reported. Explants from seedlings were transformed using Agrobacterium tumefaciens , and expression of the transgenes was demonstrated in the calli.…”
Section: Introductionmentioning
confidence: 99%
“…Published methodologies exist for obtaining callus and shoot regeneration for C. trifolii (Bakos A. et al, 1995;, C. europea (Švubová & Blehová, 2013), and C. reflexa (Srivastava & Dwivedi, 2001), and floral induction for C. reflexa (Baldev, 1962).…”
Section: Introductionmentioning
confidence: 99%